Literatura SOBRE e literatura DE: análise de relações estatísticas e conceituais - Pierotti, Maria de Lourdes Carvalho (1982)
A theory of indexing is based on the concept of aboutness in documents, that is, on the ability to recognize what a document is about. The scientist writes the literature of subject which comprises the requisite knowledge in order to do subject and the index uses the language about which leads to the requisite knowledge to know subject. Considering the existing difference between literature of and about subject and taking as literature about subject the index of a work, it is hypothezied that through the frequency of concepts contained in a literature about subject, it can be established the dominant conceptual structure of subject. For such a study, it was elaborated a distribution of the index terms of Rui Barbosa's works in alphabetical order, in a total of 5.438 terms which were submitted to several analysis. In order to measure the consistency of the index, a comparative study was made with the co-operation of some experts in Rui Barbosa who gave significant terms about the subject established weights to the index terms. A total of 5.438 terms were used for the first analysis, which reached 439 terms after the standardization of the index. The results in a way tend to prove the hypothesis although it was not possible to make any comparative analysis with similar studies. Studies of this kind may suggest answers to some problems, especially in the area of Human Sciences where the author and his work are taken as a whole. The study presents 12 tables.